Pengaruh Motivasi Intrinsik Dan Kompensasi Terhadap Kinerja Karyawan Pada PT Binayasa Karya Pratama Cabang Jakarta Melawai - Reza Rizki Ramdhani; Ratna Sari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - The purpose of this study is to determine the effect of intrinsic motivation on employee performance, to determine the effect of compensation on employee performance and to determine the effect of intrinsic motivation and compensation on employee performance at PT. Binayasa Karya Pratama Jakarta Melawai Branch. The research method uses quantitative methods. The population in this study was 55 employees so that the sample used in this study used a saturated sample with the total number of samples, namely the total population of 55 respondents. The analysis method used was a partial test (t test) and a simultaneous test (F test). The results of this study found that 1) Intrinsic motivation has a positive and significant effect on employee performance at PT. Binayasa Karya Pratama, Jakarta Melawai Branch, as evidenced by the t-value of 3.431> t-table 1.674 with a significant value of 0.001 <0.05. 2) Compensation has a positive and significant effect on employee performance at PT. Binayasa Karya Pratama, Jakarta Melawai Branch, as evidenced by the t-value of 2.467> t-table 1.674 with a significant value of 0.017 <0.05. 3) Intrinsic motivation and compensation have a positive and significant effect on employee performance at PT. Binayasa Karya Pratama, Jakarta Melawai Branch, as evidenced by the F-value of 51.852> F-table 3.175 with a significant value of 0.000 < 0.05.